2002
DOI: 10.1179/027249302125000904
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa in early adolescence in Sri Lanka

Abstract: We report four cases of anorexia nervosa (AN) seen over a period of 5 months in the psychiatry unit of a general hospital. The report is unusual because two of the patients were male, all were between 13 and 15 years of age and AN is thought to be rare in Sri Lanka. All four patients had features typical of AN. There are implications for clinical practice in Sri Lanka if the prevalence of AN is rising because all these patients presented to psychiatrists late in their illness, some in an advanced state of weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The authors concluded that misperception of weight is common among Sri Lankan adults, with males underestimating their body weight more than females. Although eating disorders are considered rare in Sri Lanka, a recent study reported four cases of anorexia nervosa in a single psychiatry unit [15]. These findings warrant proper assessment of body image perception among Sri Lankan adolescents.…”
Section: Original Articlementioning
confidence: 92%
“…The authors concluded that misperception of weight is common among Sri Lankan adults, with males underestimating their body weight more than females. Although eating disorders are considered rare in Sri Lanka, a recent study reported four cases of anorexia nervosa in a single psychiatry unit [15]. These findings warrant proper assessment of body image perception among Sri Lankan adolescents.…”
Section: Original Articlementioning
confidence: 92%
“…This similarity will permit the comparison between sexes. Although considered rare in Sri Lanka, a recent study has highlighted the occurrence of anorexia nervosa in Sri Lankan adolescents aged 13-15 years affecting both boys and girls equally [29]. However, these cases were diagnosed at a very later stage when they presented to the psychiatrist.…”
Section: Papermentioning
confidence: 99%
“…Desire to be thin is a known factor for body dissatisfaction and eating disorders [4,17]. A study has reported eating disorders among Sri Lankan adolescent girls with body image distortion [18]. However, there is no validated tool to assess the body image in Sri Lankans and there are no data about their body image construct.…”
Section: Introductionmentioning
confidence: 99%
“…While findings from East Asia have been growing steadily, research on body dissatisfaction, disordered eating, and the relationship between them in South-Asian countries, such as India and Sri Lanka, remains sparse. Only one published article on anorexia nervosa in Sri Lanka appears to exist (Perera et al, 2002). The presumption of thinness not being emphasized in South-Asian culture could be a reason for the lack of research, as “thinness was not emphasized as a requirement for feminine beauty” (Soh et al, 2006: 59).…”
Section: Introductionmentioning
confidence: 99%